1, 2, 3, 4‐Tetrahydroisoquinolines as inhibitors of HIV‐1 integrase and human LEDGF/p75 interaction. (15th March 2018) - George, Anu; Gopi Krishna Reddy, Alavala; Satyanarayana, Gedu; Raghavendra, Nidhanapati K
Abstract : Alkaloids are a class of organic compounds with a wide range of biological properties, including anti‐HIV activity. The 1, 2, 3, 4‐tetrahydroisoquinoline is a ubiquitous structural motif of many alkaloids. Using a short and an efficient route for synthesis, a series of 1, 2, 3, 4‐tetrahydroisoquinolines/isoquinolines was developed. These compounds have been analysed for their ability to inhibit an important interaction between HIV‐1 integrase enzyme (IN) and human LEDGF/p75 protein (p75) which assists in the viral integration into the active genes. A lead compound6d is found to inhibit the LEDGF/p75‐IN interaction in vitro with an IC50 of ~10 μm . Molecular docking analysis of the isoquinoline6d reveals its interactions with the LEDGF/p75‐binding residues of IN. Based on an order of addition experiment, the binding of6d or LEDGF/p75 to IN is shown to be mutually exclusive. Also, the activity of6d in vitro is found to be unaffected by the presence of a non‐specific DNA. As reported earlier for the inhibitors of LEDGF/p75‐IN interaction, 6d exhibits a potent inhibition of both the early and late stages of HIV‐1 replication. Compound6d differing from the known inhibitors in the chemical moieties and interactions with CCD could potentially be explored further for developing small molecule inhibitors of LEDGF/p75‐IN interaction having a higher potency. Abstract : An isoquinoline compound6d (ethyl‐1‐benzyl‐7‐methoxyisoquinoline‐4‐carboxylate, shown as a stick model) has been identified as a lead molecule for inhibiting the interaction between human LEDGF/p75 and HIV‐1 integrase (IN). Compound6d inhibits formation of a LEDGF/p75‐IN complex with an IC50 of 10.4 ± 3.8 μm in vitro. Similar to LEDGINs identified earlier, the activity of6d has been characterized at both the early and late stages of HIV‐1 replication. Molecular docking analysis reveals that6d occupies the LEDGF/p75 binding site on a IN dimer (the monomers are shown in red and green ribbons). The in vitro order‐of‐addition experiment supports an overlap in the binding site for LEDGF/p75 and6d on IN.